Assessment of the first 1000 3D prints requests at an academic library. Issue 1 (2nd January 2021) - Horton, Jennifer
Abstract: As academic libraries are instituting 3D printing into their services, assessment of these programs is necessary. This paper analyses the 3D printing program at an academic library from inception through the one thousandth print request. Information such as who was using the library's 3D printers, were they associated with specific departments on campus, and whether the projects used for educational or research purposes. A look at the outreach efforts to promote and education the community on 3D printing during this time period was also analyzed.